71.7k views
5 votes
Use the quadratic formula to solve the equation. -2x^2 -x+7=0

2 Answers

6 votes

Answer:

x = 1.637 or x = -2.137

Explanation:

Given equation is:

-2x²-x+7 = 0

ax²+bx+c = 0 is general quadratic equation.

x = (-b±√b²-4ac) / 2a is quadratic equation to solve the quadratic equations.

Comparing general equation with given equation , we have

a = -2 , b = -1 and c= 7

Putting the given values in quadratic formula, we have

x = (-(-1)±√(-1)²-4(-2)(7) ) / 2(-2)

x = (1±√1+56) / (-4)

x = (1±√57) / (-4)

x = (1±7.549) / (-4)

x = 1-7.549 / (-4) or x = (1+7.549) / (-4)

x = -6.549 / -4 or 8.549 / (-4)

x = 1.637 or x = -2.137 is the solution.

User Jimmy Van Beele
by
5.1k points
3 votes

Answer:
x_1=1.63\\x_2=-2.13

Explanation:

1. The quadratic formula is shown below:


x=\frac{-b+/-\sqrt{b^(2)-4ac}}{2a}

2. Given the quadratic equation given in the problem, you have that:


a=-2\\b=-1\\c=7

3. Therefore, when you substitute the values shown above, you obtain the following result:


x=\frac{-(-1)+/-\sqrt{(-1)^(2)-4(-2)(7)}}{2(-2)}


x_1=1.63\\x_2=-2.13

User Sagish
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.